Fascia iliaca compartment block for surgical analgesia in children with osteogenesis imperfecta: A retrospective cohort study - Yingxiang Xie; Long Zhang; Qing Yuan; Xueli Jiang; Qian Wang (PLoS ONE, 2026)
Background Osteogenesis imperfecta (OI) is a rare genetic bone disorder. Children with OI have a higher risk of intraoperative pain. The fascia iliaca compartment block (FICB) can reduce pain, improve intraoperative hemodynamic stability, and facilitate postoperative recovery. This study explores the feasibility and potential role of FICB in multimodal analgesia by describing its application experience in children with OI. Method This study involved children with OI who underwent surgery for femoral shaft fractures. The FICB group received ultrasound-guided FICB combined with general anesthesia, whereas the control group received general anesthesia alone. Hemodynamic parameters, serum inflammatory markers, intraoperative opioid consumption, recovery time, postoperative pain scores, and the incidence of postoperative nausea and vomiting (PONV) were recorded. Results A total of 126 children were enrolled. A significant time × group interaction was observed for changes in MAP and HR during surgery ( F 3,372 = 21.86 and F 3,372 = 16.34, both P < 0.001). At all intraoperative time points, MAP and HR were lower in the FICB group than in the Control group (all P < 0.001). A significant time × group interaction was found for postoperative VAS scores ( F 2,248 = 3.18, P = 0.04); and they were lower in the FICB group at 2, 4, and 12 hours postoperatively (all P < 0.001). CRP levels also showed a significant time × group interaction ( F 1,124 = 290.3, P < 0.001); both groups exhibited elevated postoperative CRP versus baseline ( P < 0.001), but the FICB group had lower levels. The FICB group had a shorter recovery time ( P < 0.001), lower intraoperative fentanyl and remifentanil use (both P < 0.001), and a lower incidence of PONV ( P = 0.026) compared to the Control group. Conclusion In pediatric patients with OI undergoing femoral shaft fracture surgery, ultrasound-guided FICB has the potential to enhance intraoperative hemodynamic stability, alleviate postoperative pain, and decrease the incidence of adverse reactions, thereby facilitating the implementation of optimized multimodal analgesia.